2017
DOI: 10.1097/pai.0000000000000347
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Panel of Biomarkers Between Gastric Primary Cancer and the Paired Krukenberg Tumor

Abstract: To compare a panel of selected biomarkers between gastric primary cancer and the paired Krukenberg tumor, a total of 21 cases of metastatic tumors originating from stomach and the paired gastric primary cancers were collected. The expressions of a panel of selected biomarkers were tested by IHC. FISH was used to determine the status of HER2/neu in cases scored IHC 2+. The differences of the expressions of the biomarkers were evaluated between metastatic tumors and the paired gastric primary cancers. Bcl-2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Wang et al found that during the metastasis process, specific biomarkers remain constant, such as HER2/neu, c-met, p53, and ki67, between the primary gastric tumor and the Krukenberg tumor [25]. This is a potential avenue for researchers to explore and understand how the metastasis process occurs.…”
Section: Krukenberg Tumors and Diffuse-type Gastric Adenocarcinomamentioning
confidence: 99%
“…Wang et al found that during the metastasis process, specific biomarkers remain constant, such as HER2/neu, c-met, p53, and ki67, between the primary gastric tumor and the Krukenberg tumor [25]. This is a potential avenue for researchers to explore and understand how the metastasis process occurs.…”
Section: Krukenberg Tumors and Diffuse-type Gastric Adenocarcinomamentioning
confidence: 99%